Protocol Testing with Symbolic Execution and Rule Based Specification Using Multicore Approach. (2016) - George, Sherin Mariam; Sangeetha, U.
Abstract: The implementations of network protocols are often prone to errors. These flaws lead to reduced performance, security breaches or it may bring down the entire network. Detecting such flaws is difficult because of the exponential size of the state space and many bugs manifest only after a prolonged operation. This paper focuses to detect the various types of flaws in network protocol implementation. The approach is to use the packet rules derived from protocol specification and test packets generated using symbolic execution for testing. Thus discover the violations in the implementation of network protocol DHCP. The entire system is based on these techniques and it is being evaluated on multiple cores. This procedure can be used as a general framework for testing other protocols.